2014
DOI: 10.1186/1476-4598-13-1
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expressions associated with progression of prostate cancer cells to antiandrogen therapy resistance

Abstract: BackgroundDevelopment of resistance to androgen deprivation therapy (ADT) is a major obstacle for the management of advanced prostate cancer. Therapies with androgen receptor (AR) antagonists and androgen withdrawal initially regress tumors but development of compensatory mechanisms including AR bypass signaling leads to re-growth of tumors. MicroRNAs (miRNAs) are small regulatory RNAs that are involved in maintenance of cell homeostasis but are often altered in tumor cells.ResultsIn this study, we determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
153
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(162 citation statements)
references
References 139 publications
8
153
0
1
Order By: Relevance
“…Especially germane to contemplating new targeting strategies are the key observations from several studies demonstrating a clear association of VM tumor cells expressing several stem cell markers cited above in addition to CD133 concomitant with ABCB5 drug resistance protein (Frank et al, 2011; Lai et al, 2012; Zhang et al, 2014; Lezcano et al, 2014;). Furthermore, emerging evidence indicates that conventional therapies are not effectively targeting these stem cell subpopulations, rather they are leading to their enhanced selection and growth resulting in rampant tumor progression (Hardy et al, 2015).…”
Section: Key Signaling Pathways In Vascular Mimicrymentioning
confidence: 99%
“…Especially germane to contemplating new targeting strategies are the key observations from several studies demonstrating a clear association of VM tumor cells expressing several stem cell markers cited above in addition to CD133 concomitant with ABCB5 drug resistance protein (Frank et al, 2011; Lai et al, 2012; Zhang et al, 2014; Lezcano et al, 2014;). Furthermore, emerging evidence indicates that conventional therapies are not effectively targeting these stem cell subpopulations, rather they are leading to their enhanced selection and growth resulting in rampant tumor progression (Hardy et al, 2015).…”
Section: Key Signaling Pathways In Vascular Mimicrymentioning
confidence: 99%
“…Loss of the tumor-suppressive miR-221/222 cluster enhanced migration and invasion in PCa cells targeting Ecm29, whose precise mechanisms in cancer cells remain unknown but it is involved in cancer cells invasion. Ottman et al [69], comparing androgen sensitive and resistant PCa cell lines, identified 43 miRNAs that are significantly altered during progression of PCa cells to treatment resistance, suggesting their involvement in the development of CRPC. Specific changes in miRNA expression in CRPC patients could be used as a new predictive tool for monitoring the susceptibility of development of CRPC.…”
Section: Role Of Mirnas In Prostate Cancermentioning
confidence: 99%
“…Recently, it has been observed that altered expression of miRNAs is associated with progression of androgen sensitive prostate cells to antiandrogen therapy resistance (56). Moreover, some studies described the involvement of AR signaling in the regulation of specific miRNAs in PCa (6,57).…”
Section: Discussionmentioning
confidence: 99%